Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1128/aem.00739-10
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamylmethylamide Is an Essential Intermediate in the Metabolism of Methylamine by Methylocella silvestris

Abstract: Methylocella silvestris BL2, a facultative methane utilizer, can grow on monomethylamine (MMA) as a sole carbon and nitrogen source. No activity of MMA dehydrogenase was detectable. Instead, this bacterium utilizes a methylated amino acid pathway (␥-glutamylmethylamide [GMA] and N-methylglutamate [NMG]) for MMA metabolism. The activities of the two key enzymes in this pathway, GMA synthetase and NMG dehydrogenase, were found when the bacterium was grown on MMA. GMA was detected by high-performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 38 publications
8
72
1
Order By: Relevance
“…We have previously shown that the former gene cluster was involved in MMA metabolism in M. silvestris, which encodes enzymes of the γ-glutamylmethylamide and N-methylglutamate pathway, converting MMA to formaldehyde (which is used as C and an energy source) and ammonium (which is used as an N source; Fig. 1B) (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the former gene cluster was involved in MMA metabolism in M. silvestris, which encodes enzymes of the γ-glutamylmethylamide and N-methylglutamate pathway, converting MMA to formaldehyde (which is used as C and an energy source) and ammonium (which is used as an N source; Fig. 1B) (35).…”
Section: Resultsmentioning
confidence: 99%
“…M. silvestris was grown at 25°C either in a 4-L fermentor or in 125-mL serum vials using diluted mineral salt medium as described previously (35). To test if the trimethylamine monooxygenase (tmm) mutant could grow on methylated amines, growth experiments were set up in triplicate using 120-mL serum vials, containing 20 mL medium with an inoculum size of 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13]), is a complex, multistep pathway in which the methyl group from MA is transferred to glutamate to form two novel amino acid derivatives, NMG and ␥-glutamylmethylamide (GMA), which are then oxidized to release formaldehyde (14). The NMG pathway involves at least three unique enzymes: Nmethylglutamate synthase (NMGS), N-methylglutamate dehydrogenase (NMGDH), and ␥-glutamylmethylamide synthetase (GMAS) (3,(15)(16)(17). While the enzymes involved in the NMG pathway were purified and characterized over 3 decades ago (18)(19)(20)(21)(22)(23), the genes were discovered very recently (3,15,17).…”
mentioning
confidence: 99%
“…Genes encoding enzymes and proteins for oxidation of methanol (mxa) and methylamine (mgs and mgd [5,7] but not mau genes) were identified, together with proteins and enzymes involved in pyrroloquinoline quinone synthesis and tetrahydrofolate-and tetrahydromethanopterin-linked pathways. Genes for complete serine and ethylmalonyl coenzyme A pathways (1) for carbon assimilation were identified.…”
mentioning
confidence: 99%